Endothelial Biopsy for the Diagnosis and Management of Culture-Negative Retrocorneal Fungal Keratitis With the Assistance of Optical Coherence Tomography Imaging. Issue 9 (September 2021) - Palioura, Sotiria; Tsiampali, Chara; Dubovy, Sander R.; Yoo, Sonia H.
Abstract : Purpose: To report a case of a culture-negative deep fungal corneal infection that was diagnosed after histopathology of an anterior segment optical coherence tomography–guided endothelial biopsy. Methods: A 22-year-old woman with history of contact lens wear and concomitant topical steroid use presented with a mid-stromal corneal infiltrate that failed to respond to oral acyclovir and topical fortified antibiotics. Although cornea stains, cultures, and confocal microscopy showed negative results, there was high clinical suspicion for fungal keratitis. After 2 months on topical natamycin, oral voriconazole, and serial intrastromal and intracameral voriconazole injections, the infiltrate enlarged and deepened. Imaging with anterior segment optical coherence tomography revealed that the infection had progressed to an endothelial plaque. Results: Diagnostic endothelial biopsy was performed in the operating room. Cultures showed again negative results, whereas histopathology of the removed specimen revealed fungal elements. The postoperative edema at the site of the biopsy resolved over the course of 4 weeks, and a posterior stromal scar formed. Serial intrastromal and intracameral voriconazole injections were continued for the first postoperative month. At the 1-year and the 3-year follow-up examinations, the patient's vision was 20/20 without recurrence. Conclusions: Intraoperative scraping of the endothelial plaque and histopathologic evaluation of the specimen proved to be of utmost importance for definitive diagnosis and resolution of the culture-negative deep fungal infection in this case. This young patient's cornea was retained and vision remains excellent.